Development of a Quick Response Code Integrated Echinodermata Diorama to Improve Students’ Learning Outcomes on Animalia Topics - Azmi Fathin Eka Nugraha; Zulkarnaim; Ainul Uyuni Taufiq; Asniati Jabbar (Jurnal Pendidikan Sains Indonesia, 2026)
Biology learning on the animalia topic often faces challenges due to the abstract nature of the material and the limited use of interactive and technology-integrated learning media, which may affect students’ learning outcomes. This study aimed to develop and evaluate a quick response code (QR code) integrated echinodermata diorama to improve students’ learning outcomes in animalia learning. This research employed a research and development (R&D) approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research subjects were 29 tenth-grade students of SMA Negeri 02 Bombana in the 2022/2023 academic year. Data were collected using validation sheets, student and teacher response questionnaires, and multiple-choice tests of learning outcomes. The results showed that the developed media was categorized as highly valid with a validation score of 3.66. The practicality level was very high, with scores of 86.66 from students and 89.96 from teachers. Furthermore, the effectiveness test indicated an improvement in students’ learning outcomes, with all students achieving the predetermined mastery criteria. Therefore, the QR code-integrated echinodermata diorama is feasible and recommended as an innovative learning medium for teaching animalia